Interpretation of Art : Essays on the Art Criticism of John Ruskin, Walter Pater, Clive Bell, Roger Fry, and Herbert Read. - Fishman, Solomon (UC Press voices revived., 2024)
This volume examines the criticism of five influential British writers on the visual arts--John Ruskin, Walter Pater, Roger Fry, Clive Bell, and Sir Herbert Read. Their works span a period in the history of art that ""in productivity and significance is more impressive than any other period since the Renaissance."" Each of these writers possesses extraordinary literary skills. Another common tie is their awareness of serving as spok.